Makian Referen Keadaan dalam Bahasa Melayu Jambi di Muara Bungo: Kajian Sosiolinguistik - Sri Wahyuni; Rina Marnita; Fajri Usman (Balai Bahasa Provinsi Riau, 2020)
AbstractJambi is a province in Indonesia which is divided into eleven regencies and and municipalities. One of the regencies is Bungo whose capital is Muara Bungo. Muara Bungo community uses Jambi Malay language to interact one other. This study discusses about the situational referents of swear words in Jambi Malay language. The background of the research was the habits of Muara Bungo community in using swear words to express anger, disappointment, resentment, hatred, etc. The purpose of this study is to identify, describe, and explain the situational referents of the swear words in Jambi Malay language. The data were collected by means of listening, interview, recording and note taking techniques. They were analyzed by means of distributional and identity methods. The results of the analysis of this qualitative research were presented in an informal descriptive form. They show that the situational referents of the swear words in Jambi Malay language are different from other regional languages in terms of form, naming, and function of swear words. AbstrakJambi merupakan salah satu provinsi yang ada di Indonesia. Jambi memiliki 11 kabupaten, salah satunya adalah Muara Bungo. Masyarakat Muara Bungo menggunakan bahasa Melayu Jambi untuk berinterakasi satu sama lain. Penelitian ini dilatarbelakangi kebiasaan masyarakat Muara Bungo menggunakan makian pada saat mengekspresikan rasa marah, kesal, kecewa, benci, dan lain-lainnya. Tujuan dari penelitian ini adalah untuk mengidentifikasi, menggambarkan, dan menjelaskan makian yang mengandung referen keadaan dalam bahasa Melayu Jambi. Teknik pengumpulan data menggunakan teknik simak dan teknik wawancara. Penelitian ini juga menggunakan teknik rekam dan catat. Teknik analisis data menggunakan metode padan dan agih. Penelitian ini merupakan penelitian yang menggunakan pendekatan kualitatif. Hasil analisis disajikan dalam bentuk deskriptif informal. Penemuan hasil penelitian menunjukkan bahwa makian referen keadaan dalam bahasa Melayu Jambi memiliki perbedaan dengan bahasa lainnya, yaitu dari segi bentuk, penamaan, fungsi makian.